1987
DOI: 10.1111/j.1749-6632.1987.tb23770.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid on Male Fertility

Abstract: INTRODUCUONLindsay and Medes showed in 1926 that a diet deficient in ascorbic acid (AA) for one month caused a massive degeneration of the germinal epithelium with desquamation into the lumina of the tubules in the testes of guinea pigs.' In 1941, it was reported that the seminal plasma of normal man contains 12.8 2 1.6 mg/dl of AA, which is actively concentrated and secreted by the seminal vesicles during ejaculation.24 This level is many times the 0.2-1.40 mg/dl level normally found in serum, and suggests a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 10 publications
2
47
0
4
Order By: Relevance
“…Other studies done with vitamin C only supplement that lends credence to the findings of this study are those of Dawson et al (1983Dawson et al ( , 1990 and Akmal et al, (2006) which showed that vitamin C administration improve sperm motility, count and morphology. Similarly, Yarube et al, (2008) and Afolabi et al, (2008) in their separate studies with vitamins C and E showed that the antioxidant effects of these vitamins were more remarkable when used as separate supplements, with improvements in sperm counts and related indices.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Other studies done with vitamin C only supplement that lends credence to the findings of this study are those of Dawson et al (1983Dawson et al ( , 1990 and Akmal et al, (2006) which showed that vitamin C administration improve sperm motility, count and morphology. Similarly, Yarube et al, (2008) and Afolabi et al, (2008) in their separate studies with vitamins C and E showed that the antioxidant effects of these vitamins were more remarkable when used as separate supplements, with improvements in sperm counts and related indices.…”
Section: Discussionmentioning
confidence: 49%
“…Vitamin C (known also as ascorbic acid) has been shown to be effective in treating sperm agglutination (Dawson, Harris and McGavity, 1983). 1g of daily oral vitamin C is said to help increase fertility in men who have problems with sperm agglutination, while among smokers, there was an improvement in sperm quality with vitamin C administration [Dawson, Harris and Powell, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, trial was given only for six ovulatory cycles after improvement of semen parameters. Different studies showed the positive effect of direct antioxidants in improving sperm count and motility [32][33][34][35][36][37][38][39][40][41]. Some studies showed positive effect of using vitamin E in high doses (600 and 800 IU daily) [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In men certain nutrients are essential for formation of healthy sperm. Micronutrients like vitamin C, vitamin E, L-carnitine, zinc, vitamin B complex have positive effect on both sperm count and motility [32][33][34][35][36][37][38][39][40][41]. In addition of high intake of fruits, vegetables, whole grains and nuts, supplements are also needed for noticeable effects on sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…(Greco et al, 2005;Colagar & Marzony, 2009;Mendiola et al, 2010). Ascorbic acid is found in high concentrations in seminal plasma, being proportional to its consumption (Dawson et al, 1987).…”
Section: Vitamin Cmentioning
confidence: 99%